Huperzia saururus Lam. Trevis. (Lycopodiaceae) facilitates ejaculation in spinal cord transected male rats - Birri, Marcela Alejandra (2014)
Ethnopharmacological relevance: Huperzia saururus (Lam.) Trevis. has an extensive ethnopharmacological use, mainly because of its aphrodisiac properties. The species is consumed as decoctions or infusions in traditional medicine. The purpose of the present research was to determine if Huperzia saururus is able to increase sexual potency by evaluating the ejaculatory response, in the presence of a decoction in spinal cord transected male rats.